An interview with Billy E. Jones, MD, MS. Issue 4 (2nd October 2019) - Drescher, Jack
Abstract: In the latest article of JGLMH 's Oral History Series, Emeritus Editor Dr. Jack Drescher interviews Dr. Billy E. Jones, a psychiatrist, now retired, who, among his many accomplishments, served as President and CEO of New York City's Health and Hospitals Corporation and Commissioner of the New York City Department of Mental Health. He is considered an expert on the subject of African American mental health concerns and their intersection with LGBTQ concerns, and is a past president of Black Psychiatrists of America. Dr. Drescher interviews Dr. Jones about his experiences of being openly gay as a psychiatrist, discrimination that he faced, and the changes that he has seen over his career.